[Evelyn F. Streng on Hverfjall] (1975)
Photograph of Evelyn F. Streng on Hverfjall. The dark crater is visible behind her, a dirt mound at its center. Streng stands on the rocky side of the crater wearing a brown jacket and boots, jeans, and a beanie hat. Her hand is pointed up and her weight is shifted on her right leg. A single mountain is visible in the background, dark hills and green grass surrounds it.